2014
DOI: 10.1007/s00468-014-0992-3
|View full text |Cite
|
Sign up to set email alerts
|

Sex-specific carbon and nitrogen partitioning under N deposition in Populus cathayana

Abstract: Key message Females of Populus cathayana allocated increased N to soluble proteins, while males keep N allocation pattern unchanged under N enrichment. Abstract In our study, Populus cathayana as a model species is employed to detect the sex-specific responses in growth, photosynthetic nitrogen (N) use efficiency (PNUE), carbon (C) and N partitioning when exposed to 0, 7.5 and 15 g N m -2 year -1 on the basis of local N deposition level. Our results showed that females had higher responses in photosynthesis an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
41
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 72 publications
4
41
1
1
Order By: Relevance
“…Thereafter, N began to increase after flowering in the male, but in females it carried on decreasing, leading to the greatest differences between sexes from April to August. This accords with previous studies on Rubus chamaemorus and Populus cathayana where N concentration was frequently higher in male than in female plants (Agren et al 1999;Chen et al 2014), and partly with observations on Honkenya peploides where the N concentration of females decreased from April to August, while in males a decrease was only found from April to June (Vilas and Retuerto 2016). The data in our study, however, demonstrate these changes for the first time in an evergreen dioecious woody species, and that the greatest differences in N concentration are during intensive plant growth.…”
Section: Taxus Baccatasupporting
confidence: 82%
See 4 more Smart Citations
“…Thereafter, N began to increase after flowering in the male, but in females it carried on decreasing, leading to the greatest differences between sexes from April to August. This accords with previous studies on Rubus chamaemorus and Populus cathayana where N concentration was frequently higher in male than in female plants (Agren et al 1999;Chen et al 2014), and partly with observations on Honkenya peploides where the N concentration of females decreased from April to August, while in males a decrease was only found from April to June (Vilas and Retuerto 2016). The data in our study, however, demonstrate these changes for the first time in an evergreen dioecious woody species, and that the greatest differences in N concentration are during intensive plant growth.…”
Section: Taxus Baccatasupporting
confidence: 82%
“…Carbon demand is very high during the formation and maturation of reproductive structures (McDowell et al 2000) and yet no difference was found in the C concentration of the leaves between the sexes. A similar result was observed, however, in Populus cathayana (Chen et al 2014) suggesting that this is a more general relationship in dioecious plants. Greater reproductive effort in females is probably compensated for by a higher rate of gas exchange and photosynthesis.…”
Section: Carbon Concentrationsupporting
confidence: 67%
See 3 more Smart Citations